Process Assessment of Practical Projects in Mechanical Technology Using Confirmatory Factor Analysis - Olakotan, Olusegun Olawale; Oke, Jonathan Ojo (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
The need for uniformity in assessing practical projects in mechanical technology necessitated this study. This descriptive study employing a survey focused on process assessment of practical projects in mechanical technology using Confirmatory Factor Analysis (CFA). The population for the study was 237 technical education experts in Southwest, Nigeria. There was no need for the adoption of any sampling technique since the population was manageable. The instrument for data collection was the Process Assessment Technique Questionnaire (PATQ). The instrument was validated by three experts at face and content level. The reliability of the instrument was established using Cronbach Alpha coefficient method and a coefficient of 0.93 was obtained. The data collected on the research question were analyzed using mean and Confirmatory Factor Analysis (CFA). The CFA was done using Analysis of Moment Structures (AMOS) software. The findings of the study revealed that the proposed model for assessing practical projects in mechanical technology is valid and reliable having fulfilled all the conditions for convergent, construct and discriminant validity. Average Variance Extracted (AVE) of 0.66 and Composite Reliability (CR) of 0.94 were obtained respectively. Based on the findings of the study, it was recommended that the model be adopted in assessing practical projects in mechanical technology and other related areas in Vocational and Technical Education.